Pemanfaatan Sampah Plastik Menjadi Ecobrick untuk Plang Identitas KKN UNP di Tandikek Selatan, Padang Pariaman - Zuve, Farel Olva; Andanu, Willy Novri; Rahayu, Mariyah Putri; Vega, Nadia Della; Ningsih, Fiola Sukma; Wulandari, Sefti (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
This study aims to describe the process and outcomes of transforming plastic waste into ecobricks by students of the Community Service Program (KKN) from Universitas Negeri Padang (UNP) in Tandikek Selatan Village, Patamuan District, Padang Pariaman Regency. Using a descriptive qualitative method, the research focuses on direct observation, interviews, and documentation throughout the collection of plastic waste, ecobrick production, and the installation of a village nameplate made from ecobricks. The data were analyzed narratively to capture community participation and the challenges encountered during the program. The findings show that 250 plastic bottles filled with compacted waste were successfully converted into alternative building materials, resulting in a 3x3 meter village sign. Beyond reducing plastic waste, this activity raised community awareness about environmentally friendly waste management. Strategic locations such as local food stalls served as the primary sources of recyclable waste. The project demonstrates that community-based initiatives through KKN can be an effective and creative solution for waste issues while also strengthening local identity. The use of descriptive qualitative methods effectively revealed the social and educational meaning behind the activity.